(untitled) (Research, Society and Development, 2024)
Introduction: During pregnancy, the eyes may undergo transient changes, which may, even rarely, affect visual functions. The present study aimed to understand the context and perception of ophthalmological changes in pregnant women. Methods: this is a descriptive, qualitative, and quantitative study conducted using a questionnaire via Google Forms between April and October 2023. The target population was pregnant women monitored by professionals at the Basic Health Units in Fortaleza, Ceará. The data was analyzed using Excel software and subjected to descriptive statistical analysis. Results: 52 responses were obtained from pregnant women. Most participants (69.2%) were in the third trimester of pregnancy, and most (96.2%) did not have periorbital chloasma. As for other ophthalmic changes, most pregnant women did not experience significant changes in ocular degree or intraocular pressure. A low frequency of ophthalmic consultations during pregnancy was observed, highlighting a gap in ophthalmic monitoring practices. Conclusion: the results highlight the importance of early screening for ophthalmic alterations during pregnancy, especially in pregnant women with risk factors, for more effective interventions and the promotion of maternal-fetal eye health. Raising awareness of the need for regular assessments can significantly contribute to the prevention and appropriate treatment of these alterations.